Effect of Alternative Food Combinations on the Development of Silkworms (Tubifex sp.) - Pereira, Jacob da Costa; Salvador, Mateus; Gusmão, Lucio Filipe (Journal of Basic Medical Veterinary, 2025)
Silkworm (Tubifex sp.) is one of the natural feeds that has high nutritional value and is used for fish farming. This study aims to determine the effect of the use of different types of feed on the growth of silkworms. The method used in this study is experimental with a complete random design (CRM) consisting of three treatments and one for control, test materials: tofu pulp, chicken manure, sawnut vegetable waste, plantain peel, rice field mud, Em4 and combined according to the research plan. The observed parameters include absolute biomass of the population and individual increase of the population. The results of the study showed that the treatment of each A: 1733 ind/m2 with 34.67 g/m2, B: 2067 ind/m2 with 41.33 g/m2 ,C: 3400 ind/m2 with 68.67 g/m2  and Control (K): 1567 ind/m2 with 31.33 g/m2, counting from the statistical data of the ANOVA Table shows that the Fcout is larger than the Ftable 0.05 and 0.01, which means that the difference is very noticeable with the follow-up test of Smallest Real Difference Test, Treatment C is larger, treatment B, A, K (control) treatment B is larger, treatment A and K (control) while treatment A and K (control) are not significantly different. This means that the type of feed used in treatment C has a significant influence on the increase in population biomass and the increase in the number of silkworm populations compared to others. These results can be further tested with different materials or different containers.